Integrated Implementation Conservation In DAS Serang (Study Case Institutional Group Of Land And Water Conservation Sampetan Village Subdistrict Ampel, District Boyolali) - Sochis Sochis; Soedarsono Soedarsono; Muhammad Faiqun Ni'am (International Conference on Coastal and Delta Areas, 2017)
Serang Watershed is a region dominated by steep slopes and high rainfall. This causes the region to have a high erosion potential. Water resources conservation activities in the upper watershed of Serang Watershed have been started with the construction of a number of conservation infrastructure. However, until now these efforts have not been assessed properly. This is because the existing institutional system is not functioning properly. This research discusses the strategy of conserving water resources activities in the study sites by Soil and Water Conservation Groups so that it is expected to overcome erosion problems at the research sites so as to improve the welfare of the community in the Serang watershed, especially Sampetan Village. Research method using questioner, interview, field survey, literature study, and SWOT analysis. Based from the analysis it can be concluded that by using the slovin formula, the number of respondents used as sample is 96 people from the population of 127 people consisting of various stakeholders including Village Government, Local Government, KKTA, and Community Leaders. Using SWOT method is analyzed external and internal factors of forestry and institutional resources of Sampetan Land and Water Conservation Group. Keywords : Erotion, Conservation, Institutional, SWOT.